APLIKASI PENGENALAN DAN SIMULASI ALAT MUSIK SAPE’ BERBASIS ANDROID - Kurniasaid, Ghani; Supriyono, Heru (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2018)
The development of Information and communication technology in this era has shown various result and thrive rapidly. One of the examples which can be observed in society especially on the rising generation is the using of the smartphone. The function of a smartphone is not only to send a message and give feedback on it but also to search for information. Moreover, the smartphone can be used to entertain people. A lack of the utilization of smartphone as a learning media for young generation becomes one of the problems that occur in this current globalization. The traditional musical instrument is one of the cultural heritage which is most of their connoisseur have decreased sharply. Based on that problem, we designed a simulation cellular application and introduce Sape as a traditional musical instrument with an android system for preserving the traditional musical instrument. This application will be served in a 2D form using engine game Construct 2. Multimedia Development Life Cycle (MLDC) is using as a method which contains concept, design, material collection, construction, verification, and distribution. This research used the waterfall process model as the design approach. This research is using black box method for application testing and using Likert Scale questionnaire as the data collection method. The black box method shows valid results and this application is already well functioned according to the required needs. Data collection from the questionnaire has obtained a result that equals 74.53%. It can be concluded that this application received a positive response and can help people to learn Sape’ musical instrument.